(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study was conducted to determine the profile, attitude towards school, perceived stress, anxiety level and coping mechanisms of BTLED students in Eastern Samar State University – Maydolong Campus during this pandemic. Sixty-nine (69) respondents were included in the study which utilized the descriptive survey method. Adopting a five-part questionnaire from Baloran and Cohen, the results revealed that 43 were female and 26 were male, 17 are first year, 26 are second year and 26 are third year students.49 students see themselves as poor. Most of the students agree to the stoppage of school due to pandemic, the extension of the second semester but not to the utilization of blended online learning. The respondents feel stress sometimes and moderately anxious, fearing for their health and their families. The most coping mechanism they use is following personal health measures.